Revealing new records of hypocrealean fungicolous fungi from northern Thailand - Gajanayake, Achala J.; Jayawardena, Ruvishika S.; Luangharn, Thatsanee (Phytotaxa, 2023)
Hypocreales comprise a diverse group of fungi that exhibit a wide range of lifestyles in both aquatic and terrestrial environments. A significant number of the identified fungicolous taxa belong to Hypocreales. Samples were collected from Chiang Rai and Chiang Mai Provinces during an investigation on fungicolous fungi in northern Thailand. Based on morphological characteristics and multi-gene phylogenetic analyses of ITS-LSU-tef1α-rpb2 and ITS-LSU-tub2-tef1α, two isolates were identified as Hypomyces sichuanensis (Hypocreaceae) and Mariannaea humicola (Nectriaceae) respectively. This study marks the first documentation of Hypomyces sichuanensis and Mariannaea humicola as fungicolous species from Thailand. Additionally, the study reveals a novel host record for M. humicola on Marasmius sp.